OPTIMALISASI PENETAPAN ZONASI PADA KAWASAN TAMAN NASIONAL GUNUNG GEDE PANGRANGO - , Ida Rohaida ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Zoning regulation of Gunung Gede Pangrango National Park (GGPNP) has been aimed at optimizing functions of protection, preservation and utilization of the natural resources and the ecosystem in the form of both the preservation of forest vegetation types and the rare wildlife with the habitat. The utilization of forest resources in the form of land use, plant intercropping and pine resin tapping, making an impact to restructure the management. A fairly zoning determination were needed to adapt the demands of various interests. This study aims to determine areas to allocate each of the zones in the national park that would be optimally adapt the various interests of the management. The method of spatial analysis employed was Geographical Information Systems (GIS) analysis. As for the formulation of the optimal zoning allocation, it used the Multi Objectives Programming (MOP) analysis. The result of the study reveals that the combination of the allocation of the optimal width of the zones of GGPNP based on the MOP analysis si that the core zone is 9,567.152 hectares, the wilderness zone 7,428.236 hectares, the utilization zone 1,305.356 hectares, the rehabilitation zone 3,800.567 hectares and traditional zone 749.719 hectares. Meanwhile the conservation zone for the javan gibbon and the exclusively zone have been eliminated. Regarding the combination of the zones, GGPNP has in fact supported the conservation of the montane forest by helping to preserve the flag species lives of 23 javan leopards, 54 javan hawk-eagles and 555 javan gibbons. The optimal number of visitors to the area is 68,775 person per year, contributing to the annual income of Rp 231,668,030 to the country and Rp 1,018,980 per month to the sharecroppers. This activities also contribute to the level 1 farmer (land â¤ 0.25 hectare) of Rp 109,948 a month